Nonsurgical Management of Single-Sided Deafness: Contralateral Routing of Signal - Snapp, Hillary (Journal of Neurological Surgery Part B: Skull Base, 2019)
In recent years, an increasing research effort has been directed toward remediation of single-sided deafness. Contralateral routing of signal (CROS) is the longest standing rehabilitation solution for individuals with single-sided deafness. The primary goal of CROS technology is to transfer the signal received at the deaf ear to the better hearing ear, thereby reducing the impact of the acoustic head-shadow. This allows for individuals with single-sided deafness to regain access to sounds located at the deaf ear. The hearing deficits associated with single-sided deafness are often debilitating. While surgical management of single-sided deafness is on the rise, CROS hearing aids offer a nonsurgical option to compensate for some of the deficits that occur when a listener is limited to a single ear. Limitations of early CROS devices resulted in poor adoption and acceptance in those with single-sided deafness. Following significant advances in both design and technology, the acceptance of CROS devices has increased in recent years. This paper reviews relevant literature in CROS application for the management of single-sided deafness. Technological advances, benefits, limitations, and clinical considerations are also reviewed in this article.
Keywords: CROS; contralateral routing of signal; single-sided deafness; SSD; unilateral hearing loss; hearing aid